Formation of Creative Abilities of the Future Music Teachers in their Extracurricular Activity - Saverucha, Stepan (Pedagogical Discourse, 2013)
The problems of organization of extracurricular activity of the future music teachers with the aim to form their creative abilities and the role of these processes in formation of the musician, teacher of music have been revealed in the article. The peculiarities of their application in the modern pedagogical scie nce are determined. On material of dissertation researches areexposed the different ways of forming of teaсher-musician. Particular attention is paid to reflection of the conceptual foundations foundations of organizing of this process. Creative approaches to the activity of the clubs of amateur performing arts and their role in formation of creative abilities of students have been highlighned.